ENHANCEMENT OF WATER PRODUCTION USING SOLAR DISTILLATION SYSTEM - ALI , RIAHI (2017)
Water scarcity, population increase, water pollution, and climate changes which cause flooding, drought and the pollution of water resources in the world are the main concerns for the accessibility to potable water